Гармонійний аналіз комбінованої схеми однофазного включення асинхронного електроприводу з тиристорним керуванням - Шуруб, Юрій Вікторович; Цицюрський, Юрій Леонтійович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Розроблено узагальнену для різних варіантів з`єднання силової частини електроприводу з тиристорним керуванням математичну модель комбінованої схеми однофазного включення асинхронного двигуна із змінною структурою силової частини та постійною ємністю фазозміщуючого конденсатора. Проведено порівняльний гармонійний аналіз струмів та моментів двигуна та визначено фактори, що впливають на енергоефективність електроприводу, при різних схемах включення силової частини.

Purpose. The purpose of this article isto provide a comparative analysis of influence of the phase controlled single-phase induction electric drive coordinates harmonic components on the operational characteristics of the electric drive under different variants of the power part. Methodology. A mathematical model of the combined circuit of a single-phase induction motor with a variable structure of the power part and a constant capacitance of the phase-shifting capacitor is generalized for various variants of connection of the power part of the electric drive with thyristor control. The comparative harmonic analysis of currents and torques of the motor is carried out and the factors influencing the energy efficiency ofthe electric drive at different circuit of connection of the power part are determined.Results. The analysis of the obtained data shows that the series-parallel circuit has the best harmonic composition of the consumed current in practically the whole range of changes of load torque and speed. The main effect on the loss increase is due to the asymmetry of the currents in the series-parallel circuit and the higher harmonics in the Steinmetz circuit. Originality. For the analysis of the processes in these circuits, a generalized thyristor control single-phase electric drive mathematical model, in which the structure of differential equations remains unchanged regardless of the circuit of connections of the power part, is developed. Practical value. Using of the combined circuit of single-phase switching on of a three-phase induction motor allows to use a constant capacity in the range of slips from nominal to critical without exceeding the nominal losses.
Harmonic analysis of the combined circuit of single-phase switching of induction electric drive with thyristor control
Keywords: асинхронний двигун; гармоніка; induction motor; harmonics